Two-Dimensional Hexagonal Boron Nitride Nanosheets as Lateral Heat Spreader With High Thermal Conductivity - Kong, Xiangdong; Li, Linhong; Li, Maohua; Xia, Juncheng; Wang, Yandong; Wei, Xianzhe; Xiong, Shaoyang; Gong, Ping; Pan, Zhongbin; Wu, Xinfeng; Cai, Tao; Nishimura, Kazuhito; et al. (Frontiers in Materials, 2022)
A highly thermally conductive heat spreader for the applications in electronic devices are becoming increasingly demanding and therefore the removal of excess heat requires an efficient heat dissipating device. Boron nitride nanosheets (BNNSs) were prepared as thermally conductive fillers using hexagonal boron nitride (h-BN) powder as raw material by a water exfoliation method. A composite film was prepared by vacuum filtration using cellulose nanofibers (CNFs) as the substrate with an in-plane thermal conductivity (TC) of 82.4 W m-1 K-1, thermal conductivity enhancement increasing by 9486% compared to pure cellulose film. Thus, CNF/BNNS composite films are promising as an effective thermal interface materials (TIMs) in electronic devices and electronic component applications.